Validation of a chromatographic method to routine analysis of trans-resveratrol and quercetin in red wines - Silva, Letícia Flores da; Guerra, Celito Crivellaro; Czermainski, Ana Beatriz Costa; Ferrari, Leonardo; Bergold, Ana Maria (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to validate a fast method with low-solvent use, for the analysis of trans-resveratrol and quercetin in red wines. The wines were prepared, using a classical method, from the grape (Vitis vinifera) cultivars Cabernet Franc, Cabernet Sauvignon, Malbec, Merlot, Petit Verdot, Pinot Noir, Ruby Cabernet, Syrah, Tannat, and Tempranillo. Samples were filtered and analyzed by high-pressure liquid chromatography (HPLC) with a diode array detector (DAD), at 306 and 371 nm, for trans-resveratrol and quercetin, respectively. An octylsilane column was used, and the mobile phase was composed by a gradient of methanol, water, and formic acid. The method was validated according to the following figures of merit:specificity, linearity, limit of detection, limit of quantification, precision, accuracy, and robustness. The proposed HPLC-DAD method may be established for the analysis of trans-resveratrol and quercetin in red wines.